UNMASKING THE SILENCED VOICES OF GENDER-BASED VIOLENCE AND FEMICIDES IN SOUTH AFRICAN HIGHER EDUCATION INSTITUTIONS - JK Lekganyane; LO Mphela; K Chiwarawara; Witness Maluleke (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Gender-Based Violence (GBV) and femicides within Higher Education Institutions (HEIs) are pervasive, yet often overlooked, problems affecting students and faculty worldwide. The objectives of this study were three-folded, namely; 1) The effects of GBV on victims/survivours, 2) The global recent trends of Gender-Based Violence and femicides, and; 3) The connection between GBV, sexual abuse and silenced students on campus. This qualitative study adopted the non-empirical research design: Systematic review to presents a comprehensive literature study on this phenomenon. The sample data was restricted from 2010 to 2024 (not in sequence). The inductive Thematic Content Analysis (TCA) analysed the collected data, to identified the two (02) study themes, emanating from the reviewed literature studies and the applied theoretical framework (Rational Choice Theory - RTC). This was done to shed light on its multifaceted nature, encompassing physical, psychological, financial and sexual abuse. This study confirmed the alarming cases of GBV and femicides cases within the South African HEIs, the complex dynamics perpetuating various violence were uncovered, including the institutional complicity, power imbalances, and systemic failures. This study also emphasises enduring trauma experienced by survivours and the urgent need for support and failing justice. It is recommended that proactive recommendations for policy reform and awareness campaigns remains essential to enforce efficient campus culture that actively condemns GBV and femicide against students. It is envisaged that by bringing the existing issues forefront can possibly stimulate dialogue, and change can be inducted to ultimately create safe and inclusive educational environments for all interested stakeholders.